Pengaruh Pemberian Minyak Biji Jinten Hitam (Nigella Sativa L.) Terhadap Persentase Ekspresi Interleukin-2 Pada Perokok Aktif: The Effect Of Black Cumin (Nigella Sativa L.) Seed Oil on The Percentage Of Interleukin-2 Expression In Active Smokers - Apriani, Laili; Andrey Wahyudi (Indonesian Journal of Pharmacy and Natural Product, 2024)
Cigarette smoke has the main content, namely 7,12-dimethylbenz[a]anthracene (DMBA), nicotine and tar which affect the innate and adaptive immune system. Nicotine and tar are able to suppress the expression of Interleukin-2 (IL-2) in Pheripheral Blood Mononuclear Cells (PBMC) by reducing signaling in T-cell activation. Black cumin seed oil (MBJH) both in vitro and in vivo has been used as an immunomodulatory compound containing.The main one is Timoquinone and it is expected to be able to increase IL-2. The purpose of this study was to find out how MBJH influences IL-2 expression in active smokers. A total of 36 healthy active smoker volunteers aged >18 years were divided into 4 groups. Placebo intervention and 450 mg MBJH capsules were administered for 30 days. The research design used was a single blind Randomized Controlled Trial (RCT). The percentage of IL-2 was analyzed using a flow cytometer and the average IL-2 was analyzed using Kruskal Wallis. The lowest percentage of IL-2 expression was in the placebo group with an average of 1.67%, and it increased in the 450 mg MBJH capsule group 3x1, 3x2 and 3x3 with IL-2 expression of 3.54%, 3.49% and 3.72% respectively. Conclusion in this research was the effect of MBJH administration on the percentage of IL-2 was not statistically significant, but the mean of IL-2 expression showed an increase in the group given MBJH compared to the control group given placebo.   ABSTRAK Asap rokok memiliki kandungan utama yaitu 7,12- dimethylbenz[a]anthracene (DMBA), nikotin dan tar yang mempengaruhi sistem imun bawaan dan adaptif. Nikotin dan tar mampu menekan ekspresi Interleukin-2 (IL-2) pada Pheripheral Blood Mononuclear Cell (PBMC) dengan mengurangi pensinyalan dalam aktivasi sel T. Minyak Biji Jinten Hitam (MBJH) secara in vitro maupun in vivo telah digunakan sebagai senyawa imunomodulator dengan kandungan utamanya yaitu timokuinon dan diharapkan mampu meningkatkan IL-2. Tujuan penelitian ini adalah untuk mengetahui bagaimana pengaruh MBJH terhadap ekspresi IL-2 pada perokok aktif. Sebanyak 36 relawan sehat perokok aktif dengan usia >18 tahun dibagi menjadi 4 kelompok. Intervensi plasebo dan kapsul MBJH 450 mg diberikan selama 30 hari. Desain penelitian yang digunakan yaitu Randomized Controlled Trial (RCT) single blind. Persentase IL-2 dianalisis dengan menggunakan flow cytometer dan rata-rata IL-2 dianalisis menggunakan Kruskal Wallis. Persentase ekspresi IL-2 paling rendah yaitu pada kelompok plasebo dengan rerata 1,67%, dan meningkat pada kelompok kapsul MBJH  450 mg 3x1, 3x2 dan 3x3 dengan ekspresi IL-2 berturut-turut yaitu 3.54%, 3.49% dan 3.72%. Simpulan penelitian ini adalah pengaruh pemberian MBJH terhadap persentase IL-2 tidak bermakna secara statistik, tetapi pada rerata ekspresi IL-2 menunjukkan kenaikan pada kelompok yang diberikan MBJH dibandingkan kelompok kontrol yang diberikan plasebo.